The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/d12030096
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Pattern of Species Richness among Terrestrial Mammals in China

Abstract: We describe large-scale patterns of terrestrial mammal distribution in China by using geographical information system (GIS) spatial analysis. Mammal taxa, examined by species, family, and order, were binned into 10 km × 10 km grids to explore the relationship between their spatial distribution and geographical factors potentially affecting the same. The spatial pattern of species richness revealed four agglomerations: high richness in the south, low in north, and two low richness areas in eastern and western C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…High angiosperm species diversity thus may unite the high eriophyoid mite species diversity. Our inferred species diversity centres of eriophyoid mites are further coincide with that of amphibians (Chen & Bi, 2007), birds (Lei et al., 2003), insects (Li et al., 2021) and mammals (Chi et al., 2020). This congruence among various taxonomic groups indicates that montane systems may provide relatively stable environmental conditions for speciation and survival of flora and fauna (Ding et al., 2020; López‐Pujol et al., 2011; Wang et al., 2020).…”
Section: Discussionsupporting
confidence: 76%
“…High angiosperm species diversity thus may unite the high eriophyoid mite species diversity. Our inferred species diversity centres of eriophyoid mites are further coincide with that of amphibians (Chen & Bi, 2007), birds (Lei et al., 2003), insects (Li et al., 2021) and mammals (Chi et al., 2020). This congruence among various taxonomic groups indicates that montane systems may provide relatively stable environmental conditions for speciation and survival of flora and fauna (Ding et al., 2020; López‐Pujol et al., 2011; Wang et al., 2020).…”
Section: Discussionsupporting
confidence: 76%
“…It has been found that there are over 600 species of terrestrial mammals in China (Chi et al, 2020), of which 75 species are classified as large mammals and 86 are medium‐sized mammals. Our study analyzed the habitat patches of 64 large mammals and 48 medium‐sized mammals, which account for 85.33% and 55.81% of the large mammals and medium‐sized mammals in China.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, there are studies that explained the distribution of glires in China (Xing, 2008;Zhou, 2000), and the mechanism that determines richness patterns were initially discussed. Chi et al (2020Chi et al ( , 2021 studied the distribution pattern of terrestrial mammal abundance in China and its relationship with environmental factors. Inevitably, these studies did not take sufficient account of glires distribution patterns, especially the endemic and nonendemic glires groups in China.…”
Section: Introductionmentioning
confidence: 99%